OROPHARYNGEAL DYSPHAGIA: AN ASSOCIATION BETWEEN DYSPHAGIA LEVEL, SYMPTOMS AND COMORBIDITY - Bedaque, Henrique; Lidiane Maria de Brito Macedo Ferreira; Fernandes, Kallil Monteiro; Godoy, Cynthia Meira de Almeida; Magalhães Junior, Hipólito Virgilio (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: Associate levels of dysphagia according to the patient health condition. Methods: Retrospective study analyzing 149 medical records of patients who underwent Fiberoptic endoscopic evaluation of swallowing (FEES) in a tertiary hospital from 2016 to 2018. Data was collected on symptoms, comorbidities, FESS findings and oropharynx dysphagia classification. Statistical analysis was performed through descriptive and bivariate analysis using the Chi-square and Fisher's exact tests with a 5% significance level. Results: Most patients are elderly, female and with the main complaint of gagging for liquids and solids (30.9%), and gagging only for liquids was associated with the presence of mild dysphagia. The most prevalent degree of oropharynx dysphagia (OD) was mild (45%). In relation to patients' diseases, associations were identified between amyotrophic lateral sclerosis and mild dysphagia, Parkinson's disease and moderate dysphagia, and past pneumonia and / or head and neck cancer with severe dysphagia. Conclusions: The main complaint of patients with dysphagia and their pathological history should guide the treatment, without dispensing with complementary exams such as FESS, highlighting Parkinson's disease with moderate oropharynx dysphagia and past pneumonia and / or head and neck cancer as severe dysphagia.